Open Resonator System for Reflectarray Elements Characterization - G. Di Massa; S. Costanzo; O. H. Moreno (International Journal of Antennas and Propagation)
An open resonator system is proposed in this work to study the phase behavior of reflectarrays cells. The characterization of the single reflectarray element is performed by assuming a Gaussian plane wave normally incident on an infinite periodic array of identical radiating elements. An equivalent circuit model is properly derived for the open cavity including the reflectarray test structure, in order to retrieve the phase design curve of the single reflectarray element. K-band experimental validations are presented and discussed to show the effectiveness of the approach.